Experimentally Induced Empathy Has No Impact on Generosity in a Monetarily Incentivized Dictator Game - Lönnqvist, Jan-Erik; Walkowitz, Gari (Frontiers in Psychology, 2019)
In a monetarily incentivized Dictator Game we expected Dictators’ empathy towards the Recipients to cause more pro-social allocations. Empathy was experimentally induced via a commonly used perspective taking task. Dictators (N = 474) were instructed to split an endowment of 10€ between themselves and an unknown Recipient. They could split the money 8/2 (8€ for Dictator, 2€ for Recipient) or 5/5 (5€ each). Although the empathy manipulation successfully increased Dictators’ feelings of empathy towards the Recipients, Dictators’ decisions on how to split the money were not affected. We had ample statistical power (above .99) to detect a typical social psychology effect (corresponding to r around .20). Other possible determinants of generosity in the Dictator Game should be investigated.